Application of Business Model Canvas in MSMEs in Karangwuni Village - Hernawan, Adam; Savandha, Septien Dwi; Karsa, Aldo Hermaya Aditia Nur; Asikin, Muhamad Zaenal; Fadilah, Muhamad Opan (International Journal of Social Service and Research, 2024)
This qualitative research, employing a literature review approach, examines the pivotal role of Micro, Small, and Medium Enterprises (MSMEs) in fostering economic development amidst the ongoing wave of globalization. Specifically focused on Karangwuni Village, the study elucidates how the adoption of the Business Model Canvas framework positively impacts MSMEs, fortifying their operational infrastructure and catalyzing avenues for sustainable expansion, thereby underscoring the significance of strategic frameworks in bolstering the resilience and growth trajectory of MSMEs within the broader economic landscape.